Station-Keeping Simulation and Planning for LAPAN-A4 Satellite Using Finite-Burn Thruster - Zuhri, Muhammad Rizki; Poetro, Ridanto Eko (Indonesian Journal of Aerospace, 2021)
To be a Sun-synchronous orbit (SSO), the orbit must have a certain value of nodal precession rate, which equals to 360°/year. However, the value of nodal precession rate is usually drifted by orbit perturbations, mainly by the oblateness of the Earth and atmospheric drag, to be no longer 360°/year as expected for SSO. Thus, the local time of the satellite will change too, so it needs to be corrected by some correction maneuvers. In this research, the authors studied about station-keeping planning for SSO satellite via inclination correction maneuver by simulation using GMAT, a software developed by NASA, with a finite-burn propulsion approach. In this research, LAPAN-A4 satellite is chosen to be the satellite that will be simulated. Some alternative plans of inclination correction maneuver based on maneuvering periods are chosen, they are maneuver for every 2 months, 4 months, 6 months, 12 months, and 24 months. The simulation results show that the optimal station keeping planning is the maneuver for every 2 months. This alternative gives the lowest fuel consumption so that the fuel and launch cost will be minimum, and the local time drift that is still may be tolerated.